FAMILY AND PEERS MATTER: WHAT DRIVES UNDERGRADUATES’ INTENT TO BECOME TEACHERS - Yusqi Alfi Habibah; Shendy Andrie Wijaya; Neviyani (CV. TOTUS TUUS, 2026)
Education systems rely on teachers as key agents of learning, yet many undergraduates—even in teacher-education pathways—report waning interest in teaching. Grounded in social-context perspectives, this study examines whether family environment and peer relationships shape students’ interest in becoming teachers at Universitas PGRI Argopuro Jember. The objectives were to (1) estimate the partial effects of family environment and peer relationships and (2) assess their simultaneous influence on teaching interest. A quantitative survey was administered to a purposive sample of 96 students from the 2021 cohort (population = 2,480). Data were gathered via Likert-scale questionnaires and analyzed in SPSS through data screening, classical assumption tests, and multiple linear regression. Instruments demonstrated high internal consistency (α = .918, .930, .909). Assumptions were met (e.g., Kolmogorov–Smirnov p = .200; VIF = 1.214; Glejser p > .05). The regression model showed that both family environment () and peer relationships () positively and significantly predict interest in becoming a teacher, with family exerting the stronger effect; the model explained 31.5% of variance (). These findings indicate that strengthening family support and cultivating constructive peer climates can bolster students’ teaching interest. Practically, programs should integrate parent-partnership orientations and peer mentoring/communities of practice alongside early mastery experiences (e.g., micro-teaching, supervised practicums). Future studies should employ longitudinal or SEM/PLS-SEM designs to test mediated–moderated pathways (e.g., self-efficacy, task values) and conduct multi-group analyses by gender, SES, or practicum exposure, complemented by qualitative inquiry into family and peer meaning-making about the profession. Education systems rely on teachers as key agents of learning, yet many undergraduates—even in teacher-education pathways—report waning interest in teaching. Grounded in social-context perspectives, this study examines whether family environment and peer relationships shape students’ interest in becoming teachers at Universitas PGRI Argopuro Jember. The objectives were to (1) estimate the partial effects of family environment and peer relationships and (2) assess their simultaneous influence on teaching interest. A quantitative survey was administered to a purposive sample of 96 students from the 2021 cohort (population = 2,480). Data were gathered via Likert-scale questionnaires and analyzed in SPSS through data screening, classical assumption tests, and multiple linear regression. Instruments demonstrated high internal consistency (α = .918, .930, .909). Assumptions were met (e.g., Kolmogorov–Smirnov p = .200; VIF = 1.214; Glejser p > .05). The regression model showed that both family environment () and peer relationships () positively and significantly predict interest in becoming a teacher, with family exerting the stronger effect; the model explained 31.5% of variance (). These findings indicate that strengthening family support and cultivating constructive peer climates can bolster students’ teaching interest. Practically, programs should integrate parent-partnership orientations and peer mentoring/communities of practice alongside early mastery experiences (e.g., micro-teaching, supervised practicums). Future studies should employ longitudinal or SEM/PLS-SEM designs to test mediated–moderated pathways (e.g., self-efficacy, task values) and conduct multi-group analyses by gender, SES, or practicum exposure, complemented by qualitative inquiry into family and peer meaning-making about the profession.